Nilai Kemanusiaan dalam Proses Belajar Desain Interior Partisipatif yang Berpusat pada Pengguna: Studi kasus pada desain interior panti jompo - Tumilar, Elaine Steffanny (Program Studi Desain Interior Unikom, 2019)
ABSTRACT This paper focuses on discussing the method of Participatory Design for Public Space as a learning method for students in an Interior Design study program using case studies of designing nursing homes. The main issue is that many nursing homes in Indonesia have not been designed according to the standards, which the users need. What becomes vital here is that problems need to be solved in more specific ways. Branches of Social Science that uphold human values, such as Psychology in this case, began to be incorporated into the process of designing nursing homes. Over time, due to the development of knowledge in an academic environment and also society at large, interior designers have started to realize the importance of using empathy as an instrument adopted from social science. The goal is to produce designs that are meaningful and appropriate for use in the ideal conditions for the users themselves. The overall results of this study will be demonstrated through the exploration of learning from an academic institution that is enriched by involving the user communities. Students are faced with practical exploration, which requires them to manifest their existing scientific knowledge in a real life situation. This form of learning is implemented in Interior Design studies with a Participatory approach that emphasizes human behavior as the users who actually occupy the space and indeed its surrounding environment. Keywords: Interior Design education, participatory design, nursing homes.